KAJIAN YURIDIS GUGATAN PEMBATALAN AKTA PEMINDAHAN DAN PENYERAHAN HAK ATAS TANAH DENGAN GANTI RUGI YANG DIBUAT DIHADAPAN NOTARIS (BERDASARKAN PUTUSAN MA NOMOR 80/PDT.G/2015/PN.LBP) - ANANDAR RITONGA (PREMISE LAW JURNAL, 2016)
Notarial acts have to be authentic evidence when there is a dispute in the Court; they provide legal guarantee, order, and protection for the people who use notaries service. The objective of the research was to find out legal protection for a notary as public official who draws up deed formallyand materially according to law no.30/2004 om notarial fuction and to find out the legal consequence for a notary in drawing up certificates no. 1 and no. 2 on april 2013, based on the rullingof lubuk pakam distric court (putusan MA no.80/Pdt.G/2015/PN.Lbp) in conjuction with law no. 30/2004 on notarial fuction. Legal protection for a notary which is asked as a witness by investigators, prosecutors, and judges is regulated in article 66 of law no20/2004 on notarial fuction. Keywords : Legal Protection, Dispute, Deed